2017
DOI: 10.18632/oncotarget.18709
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hepatectomy and palliative local treatments for gastric cancer patients with liver metastases: a propensity score matching analysis

Abstract: BackgroundThe optimal treatments for gastric cancer with liver metastases (GCLM) remain controversial. This study aimed to evaluate the efficacy of hepatectomy, RFA and TACE as local treatments for GCLM.MethodsFrom 2001 to 2015, 119 consecutive patients who received multidisciplinary treatments based on curative gastrectomy and local treatments (hepatectomy, RFA and TACE) for liver metastases were enrolled in this retrospective cohort study. Patients were divided into Group A (46, hepatectomy) and Group B (73,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 27 publications
0
17
2
Order By: Relevance
“…Also, hepatic bilobar dissemination is a factor linked to worse prognosis[ 15 , 27 , 30 , 34 , 39 , 47 ]. Interestingly, in contrast to the literature, a recent report[ 38 ] indicated how the distribution and number of liver metastases do not significantly impact on survival. This would present future therapeutic opportunities even in H2-H3 patients.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Also, hepatic bilobar dissemination is a factor linked to worse prognosis[ 15 , 27 , 30 , 34 , 39 , 47 ]. Interestingly, in contrast to the literature, a recent report[ 38 ] indicated how the distribution and number of liver metastases do not significantly impact on survival. This would present future therapeutic opportunities even in H2-H3 patients.…”
Section: Resultsmentioning
confidence: 75%
“…Only one study[ 15 ] reported minor survival for patients with proximal gastric tumors compared to a distal site. This could be closely related to the increased aggressiveness of cardia as opposed to antral gastric tumors, but none of the several recent papers has confirmed these data[ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] Recent studies support hepatectomy (Hp) as an alternative in selected patients with GCLM, with promising results of 5-year survival rates of about 30%. [7][8][9][10] However, Hp in the treatment of gastric carcinoma liver metastases (GCLM) is still controversial. 6 Many studies aimed at validating clinical factors associated with longer survival, as a result of more indolent biology of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] And a study comparing hepatectomy and palliative local treatments for gastric cancer patients with liver metastasis reveals that according to the propensity score matching analyses, TACE achieves a similar survival benefit in patients compared with RFA and requires markedly less average cost. [ 24 ] These studies all indicate a potential benefit of TACE in gastric cancer patients. However, to our best knowledge, there is still no study evaluating the efficacy and safety of DEB-TACE in gastric cancer, in this study, we only included 2 gastric cancer patients receiving DEB-TACE alone due to that the cases are sporadic in clinical practice, and both the 2 patients were treated with DEB-TACE alone.…”
Section: Discussionmentioning
confidence: 90%